Poetry a survivor's guide - Yakich, Mark (Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2022)
"Playful and serious, unforgiving and compassionate, Poetry: A Survivor's Guide offers an original take on a subject both loved and feared. In a series of provocative and inspiring propositions, the act of reading a poem is made new, and the act of writing one is made over. Questions of poetry's difficulty, pretension, and relevance are explored with insight and daring. In an age of new media and social networking, this handbook-cum-manifesto provides fresh reverence for one of our oldest forms of art"--Provided by publisher.